2021
DOI: 10.1039/d1qm00414j
|View full text |Cite
|
Sign up to set email alerts
|

A long-term controlled release of the drug for osteoporosis from the surface of titanium implants coated with calcium zeolite

Abstract: The aim of this study was to prepare an implant material enabling a slow, gradual and gentle release of risedronate. Such material was designed to allow the sorption of large...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The layer was prepared based on a previously described methodology [ 6 ]. Initially, the titanium alloy, Ti6Al4V, was subjected to abrasion with 120 grit sandpaper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The layer was prepared based on a previously described methodology [ 6 ]. Initially, the titanium alloy, Ti6Al4V, was subjected to abrasion with 120 grit sandpaper.…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary to replace the weakened bone with an implant. Therefore, it is necessary to look at the prospects related to the possibility of modifying the surface of materials intended for their production in order to improve their properties and positively influence the regeneration process and osseointegration [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the BPCCs previously reported, nanocrystals of a zoledronate (ZOLE)-based BPCC (ZOLE-Ca form II) named nano -Ca@ZOLE have demonstrated the greatest potential as therapy for the treatment and prevention of OM. , Compared to other BPCCs, these presented higher thermal and structural stability in physiological media, higher binding affinity (∼2.5 x more than ZOLE) to hydroxyapatite in a relevant time frame (24 h), and higher cytotoxicity effects even at the lowest concentrations against a cancerous cell line model (MDA-MB-231) without inducing any negative effect in normal osteoblast-like cells (hFOB 1.19). , Additionally, compared to other BPs such as alendronate and risedronate, reports on immobilization attempts of ZOLE or its derivatives in titanium surfaces have not been reported. , …”
Section: Introductionmentioning
confidence: 99%
“…Titanium implants coated with calcium zeolite were used as controlled delivery systems (CDSs) for the drug risedronate (RIS). It was found that one year is needed for the release of 30% of the total drug quantity [6]. Biphasic calcium phosphate (BCP) scaffolds were loaded with the drug alendronate (ALE).…”
Section: Introductionmentioning
confidence: 99%